Analisis Pengaruh Leverage Terhadap Nilai Perusahaan Dengan Kepemilikan Manajerial Dan Arus Kas Bebas Sebagai Variabel Pemoderasi - Linawaty; Agustin Ekadjaja (Jurnal Ekonomi, 2017)
The purpose of this study is to examine whether or not the effect of leverage on firm value with management ownership and free cash flow as moderating variable practice of manufacturing firms listed in the Indonesian Stock Exchange for the period 2012-2014. Thirty-five samples are selected by purposive sampling and used the ordinary least square method to analyse. This study used secondary data such as the firm financial statements published during the observation year. The dependent variable in this study is the firm value practice of real estate firms listed on the Indonesian Stock Exchange, while the independent variables are leverage, management ownership, and free cash flow. The result shows that the impact of leverage is significant on firm value; Free Cash Flow is significant moderating leverage on firm, Management Ownership is not significant moderating leverage on firm value